PhiReX: a programmable and red light-regulated protein expression switch for yeast. Issue 15 (26th July 2017) - Hochrein, Lena; Machens, Fabian; Messerschmidt, Katrin; Mueller-Roeber, Bernd
Abstract: Highly regulated induction systems enabling dose-dependent and reversible fine-tuning of protein expression output are beneficial for engineering complex biosynthetic pathways. To address this, we developed PhiReX, a novel red/far-red light-regulated protein expression system for use in Saccharomyces cerevisiae . PhiReX is based on the combination of a customizable synTALE DNA-binding domain, the VP64 activation domain and the light-sensitive dimerization of the photoreceptor PhyB and its interacting partner PIF3 from Arabidopsis thaliana . Robust gene expression and high protein levels are achieved by combining genome integrated red light-sensing components with an episomal high-copy reporter construct. The gene of interest as well as the synTALE DNA-binding domain can be easily exchanged, allowing the flexible regulation of any desired gene by targeting endogenous or heterologous promoter regions. To allow low-cost induction of gene expression for industrial fermentation processes, we engineered yeast to endogenously produce the chromophore required for the effective dimerization of PhyB and PIF3. Time course experiments demonstrate high-level induction over a period of at least 48 h.